Expression of Tau Produces Aberrant Plasma Membrane Blebbing in Glial Cells Through RhoA-ROCK-Dependent F-Actin Remodeling - Torres-Cruz, Francisco M; Rodríguez-Cruz, Fanny; Escobar-Herrera, Jaime; Barragán-Andrade, Norma; Basurto-Islas, Gustavo; Ripova, Daniela; Ávila, Jesús; Garcia-Sierra, Francisco (Journal of Alzheimer's disease, 2016)
Abnormal aggregation of Tau in glial cells has been reported in Alzheimer's disease (AD) and other tauopathies; however, the pathological significance of these aggregates remains unsolved to date. In this study, we evaluated whether full-length Tau (Tau441) and its aspartic acid421-truncated Tau variant (Tau421) produce alterations in the normal organization of the cytoskeleton and plasma membrane (PM) when transiently expressed in cultured C6-glial cells. Forty-eight hours post-transfection, abnormal microtubule bundling was observed in the majority of the cells, which expressed either Tau441 or Tau421. Moreover, both variants of Tau produced extensive PM blebbing associated with cortical redistribution of filamentous actin (F-Actin). These effects were reverted when Tau-expressing cells were incubated with drugs that depolymerize F-Actin. In addition, when glial cells showing Tau-induced PM blebbing were incubated with inhibitors of the Rho-associated protein kinase (ROCK) signaling pathway, both formation of abnormal PM blebs and F-Actin remodeling were avoided. All of these effects were initiated upstream by abnormal Tau-induced microtubule bundling, which may release the microtubule-bound guanine nucleotide exchange factor-H1 (GEF-H1) into the cytoplasm in order to activate its major effector RhoA-GTPase. These results may represent a new mechanism of Tau toxicity in which Tau-induced microtubule bundling produces activation of the Rho-GTPase-ROCK pathway that in turn mediates the remodeling of cortical Actin and PM blebbing. In AD and other tauopathies, these Tau-induced abnormalities may occur and contribute to the impairment of glial activity.
Keywords: Cell Line; tau Proteins; signální transdukce; glial degeneration; Rats; proteiny tau; Rho associated protein kinase; Actins; transfekce; Cell Membrane; Tau; Microscopy, Confocal; Neuroglia; Signal Transduction; aktiny; neuroglie; krysa rodu Rattus; konfokální mikroskopie; Green Fluorescent Proteins; western blotting; tauopathies; rho-Associated Kinases; kinázy asociované s Rho; Blotting, Western; F-Actin remodeling; rhoA protein vázající GTP; cytoplazma; Tubulin; zvířata; elektroforéza; Electrophoresis; Guanine Nucleotide Exchange Factors; rhoA GTP-Binding Protein; zelené fluorescenční proteiny; koncové značení zlomů DNA in situ; Transfection; buněčná membrána; In Situ Nick-End Labeling; Fluorescent Antibody Technique; buněčné linie; Cytoplasm; tubulin; RhoGTPases; membrane blebbing; výměnné faktory guaninnukleotidů; fluorescenční protilátková technika; Animals